2019
DOI: 10.3889/oamjms.2019.118
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge, Attitudes, and Practice of Medical Students Regarding the Risk of Hepatitis B Virus Infection and Control Measures at Qassim University

Abstract: BACKGROUND: Medical students are exposed to occupational health hazards in hospitals during their studies and lack sufficient education about infection control measures. Injury to medical students is a substantial problem and students have an increased risk of hepatitis B virus (HBV). To understand how medical students think about infection control, it is important to identify the strengths and weaknesses of their education. AIM: To assess current knowledge, attitudes, and practice of medical students re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 22 publications
3
10
1
1
Order By: Relevance
“…This could have been due to training gaps, the need to properly orient or "on board" employees and inexperience of new staff. 5,8,9,11 Studies have noted that sharp injuries are high in nursing personnel, as found in this study. 8,9 In fact, Chadee et al in 1999 noted that most injuries occurred in nurses in Trinidad and Tobago.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This could have been due to training gaps, the need to properly orient or "on board" employees and inexperience of new staff. 5,8,9,11 Studies have noted that sharp injuries are high in nursing personnel, as found in this study. 8,9 In fact, Chadee et al in 1999 noted that most injuries occurred in nurses in Trinidad and Tobago.…”
Section: Discussionsupporting
confidence: 68%
“…Both studies looked at sharp injuries but Alay et al also looked at blood and body fluid exposure, similar to the secondary objective in our study. 8,9 The younger age group seen in this study could be due to lack of experience. The higher predominance of females, in this study could also have been due to the fact that females represent a larger part of the workforce, particularly in wards maids and nurses.…”
Section: Discussionmentioning
confidence: 89%
“…A similar result was observed in a study done in a Syrian private university and in a study done in Qassim University, in which students had poor knowledge about HBV but believed that medical students had a higher risk of infection contraction. [ 11 16 ] It also revealed that male students had a higher level of knowledge about HBV transmission when compared to female students. These findings are not in line with a study conducted at King Khalid University Hospital (KKUH) in Riyadh, Saudi Arabia, in which females had a higher level of knowledge than males.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] While Locally, one cross-sectional study done at Unaizah College of Medicine, Qassim, found that only 21% of 321 students had good knowledge about HBV infection and prevention and only 41.4% of the students were vaccinated against HBV. [ 11 ] Another local study was done at King Khalid University Hospital (KKUH), Riyadh. The study revealed that 46.5% of 444 students had a high level of knowledge about HBV and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…O segundo estudo realizado com 321 estudantes do curso de medicina avaliou o conhecimento dos estudos sobre a contaminação pelo vírus da hepatite B. A maioria dos estudantes tinha pouco conhecimento, atitudes e prática em relação ao risco de infecção pelo vírus da hepatite B e arecomendação dos autores foia implementação de uma política de treinamento em prevenção de infecções Development, v. 9, n. 8, e207985254, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5254 para todos os estudantes de medicina antes de iniciar a prática clínica (Al Wutayd et al, 2019). No Brasil, as diretrizes curriculares dos cursos de graduação da área da saúde preveem a transversalidade na abordagem nas medidas de controle de infecção durante todo o processo formativo.…”
Section: Abordagemunclassified